2012
DOI: 10.1016/j.hedp.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic electron transport in non-equilibrium warm dense gold

Abstract: openAccessArticle: FalsePage Range: 303-303doi: 10.1016/j.hedp.2012.01.002Harvest Date: 2016-01-12 15:10:57issueName:cover date: 2012-09-01pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Such experiments, based on the Fourier Domain Interferometry technique, are currently available. 15 The ab initio parameterized 2T-MD methodology with a T e -dependent potential described here can be readily applied to describe and understand photoinduced phase transitions in different metal films.…”
Section: -9mentioning
confidence: 99%
See 1 more Smart Citation
“…Such experiments, based on the Fourier Domain Interferometry technique, are currently available. 15 The ab initio parameterized 2T-MD methodology with a T e -dependent potential described here can be readily applied to describe and understand photoinduced phase transitions in different metal films.…”
Section: -9mentioning
confidence: 99%
“…5,7 In particular, the femtosecond structural evolution of photoexcited gold and other metals has been studied recently both experimentally and theoretically. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Different regimes of excitation have been identified, depending on the energy deposited by the laser pulse in a gold nanofilm: a low-fluence regime in which sample does not melt, where coherent acoustic phonon generation is observed; 13 a medium-fluence regime in which the sample undergoes melting, where a competition between homogeneous and heterogeneous melting is identified; 9 a high-fluence regime in which electronic effects are expected to affect the melting process. 10,11,22 The initial stages of the dynamics are extremely difficult to unravel and recent results still stir a lot of controversy 10,11,14,15 even for relatively simple gold nanofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include Joule heating and dissipation in solid-state and molecular physics [1,2], equilibration of warm dense matter generated by laser pulses [3][4][5], and radiation cascades [6]. The interest in coupled dynamics of out-of-equilibrium electrons with vibrations occurs in several fields, including transport in molecular junctions [7,8] and photoelectron spectroscopy [9], and has triggered the development of new experimental techniques [10].…”
Section: Introductionmentioning
confidence: 99%
“…This process usually lasts several picoseconds or longer until the T e drops much lower than the vacuum level after electron-phonon thermalization and the electrons lose energy via TE. On the back, the number of TE electrons could be significantly less than that on the front if electron transport across the film has been somehow impeded [27,28]. Overall, the intensity of MPPE is proportional to the fourth power of pump intensity, whereas that of TE depends linearly on the total absorbed energy.…”
mentioning
confidence: 99%
“…These studies have revealed that under the intense pump conditions of the widely used idealized slab plasma approach to create single-state WDM [20,21] in the laboratory, significant numbers of hot electrons can be ejected from WDM targets by thermionic emission (TE), multiphoton photoemission (MPPE), or thermally assisted MPPE [22][23][24][25][26]. This ejection may break the charge neutrality and reduce the excitation energy density in the targets [27], thus altering the subsequent formation and characteristics of WDM [15,28]. To address these important issues, we conducted a systematic measurement of the ejected charge cloud dynamics in the vicinity of a warm dense (WD) gold nanofilm using ultrafast electron shadow imaging and deflectometry in a single-shot mode.…”
mentioning
confidence: 99%